The Impact of Transactional and Transformational Leadership Style on Organizational Citizenship Behaviors - Rodrigues,Alexandra de Oliveira (2015)
Abstract We investigated the impact of transactional and transformational leadership styles on organizational citizenship behaviors. The sample consisted of 213 workers of both genders who answered the Multifactorial Leadership Scale and the Organizational Citizenship Behaviors (OCB) Scale. The multiple linear regression showed that: the transactional leadership style positively predicted the OCB dimension associated to the creation of a climate favorable to the organization in the external environment; the transformational leadership style positively predicted the dimensions of OCB associated to the creative suggestions related to the system; to the creation of a favorable organizational climate in the external environment; to self-training and to cooperation among colleagues; transformational leadership style showed greater predictive power on OCB than transactional leadership. It was concluded that transformational leaders are more capable to lead their subordinates in order to take actions that go beyond their prescribed roles.